2019
DOI: 10.1021/acsearthspacechem.9b00083
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Dissolved Lead Sources in the Canadian Arctic: Insights from the Canadian GEOTRACES Program

Abstract: This study addresses an important knowledge gap in the distribution of lead (Pb) in the Arctic Ocean, by presenting dissolved Pb concentrations from samples collected during the GEOTRACES Canadian cruise in 2015. Dissolved Pb showed an increase in concentration from the Canada Basin toward Baffin Bay and the Labrador Sea. Canada Basin was the most isolated region from anthropogenic Pb inputs with low background concentrations (1.4−6.2 pmol kg −1 ) across most of the basin, although higher Pb features from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 91 publications
3
21
0
Order By: Relevance
“…In addition to the particulate trace metal enrichment documented here, a similar glacially derived peak of dissolved lead and Mn has been described at station CAA1 (Colombo et al, 2020;Colombo, Rogalla, et al, 2019), and adds to the growing evidence that glacial meltwater runoff could be a significant source of Fe and other trace elements to coastal waters (Bhatia et al, 2013;Kanna et al, 2020). Baffin Bay and the Labrador Sea are surrounded by extensive glacial ice-sheets (e.g., Greenland, Ellesmere Island, Devon Island, Baffin Island), and therefore, receive large amounts of glacial meltwaters and associated trace elements (Bhatia et al, 2013;Kanna et al, 2020).…”
Section: Glacial Runoff Along Devon Island Coastsupporting
confidence: 78%
See 2 more Smart Citations
“…In addition to the particulate trace metal enrichment documented here, a similar glacially derived peak of dissolved lead and Mn has been described at station CAA1 (Colombo et al, 2020;Colombo, Rogalla, et al, 2019), and adds to the growing evidence that glacial meltwater runoff could be a significant source of Fe and other trace elements to coastal waters (Bhatia et al, 2013;Kanna et al, 2020). Baffin Bay and the Labrador Sea are surrounded by extensive glacial ice-sheets (e.g., Greenland, Ellesmere Island, Devon Island, Baffin Island), and therefore, receive large amounts of glacial meltwaters and associated trace elements (Bhatia et al, 2013;Kanna et al, 2020).…”
Section: Glacial Runoff Along Devon Island Coastsupporting
confidence: 78%
“…At CAA1 station, a unique subsurface plume highly enriched in dissolved and particulate Fe, as well as pAl, pV, and pMn, was present between approximately 30 and 200 m ( σ θ = 25.92–27.15; Figures 3 and 4), at the same density range where transmissivity values dropped and Chl‐a increased (Colombo, Rogalla, et al., 2019). This subsurface feature is most probably related to sediment‐laden meltwater inputs from glaciers along the western side of Devon Island (Lenaerts et al., 2013; Figure 5b), which deliver extremely high loads of particulate and dissolved elements (e.g., dFe: 212 nM, pFe: 13,980, pAl: 19,355, and pMn: 151 μg L −1 ; Colombo, Brown, et al., 2019) to CAA1 station, located 5 km offshore of the Devon coast (Figure 5b).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Based on available data from GEOTRACES cruise GA01 sampling the West Greenland Current entering the Labrador Sea off the southern tip of Greenland, concentrations of dFe, dMn, dCo and dCu in the Baffin Current were almost consistently higher, up to one order of magnitude in the case of dMn, than those observed in the water column of the West Greenland Current, the only notable exception being dFe in Surface Water of the Baffin Current at 150 and 200 m depth (Figure S9 in Supporting Information S1). Consequently, a strong gradient in dissolved micronutrient concentrations between regions influenced by the North Atlantic inflow (along the West Greenland coastline) and Arctic Ocean outflow (coastal Canada) is expected in Davis Strait (Colombo et al, 2019(Colombo et al, , 2020. Calculating micronutrient fluxes only from concentrations of dFe, dMn, dNi, dCu, dZn and the labile fraction of dCo in the Baffin Current herein likely overestimates Arctic contributions to outflow across Davis Strait.…”
Section: Arctic-atlantic Flux Estimatesmentioning
confidence: 99%
“…While not evident at CAA9, elevated proportions of Pacific NO 3 − deriving from remineralization were otherwise apparent at CAA1 and CAA5 (discussed below), suggesting that the remineralized Pacific NO 3 − at CAA6 is imported from northern Lancaster Sound. Based on measurements of dissolved lead and other tracers along the same hydrographic line, Colombo et al (2019) similarly concluded that water column properties at CAA6 showed traceable input from Lancaster Sound, entrained across Barrow Strait as part of the westward counter-current in northern Parry Channel. This conclusion is contrary to previous notions, however, as the T-S characteristics suggest that the westward flow from Lancaster Sound does not penetrate further west than Resolute Bay (Jones & Coote, 1980;.…”
Section: The Dominant Influence Of Mixing On Subsurface No 3 − In The...mentioning
confidence: 98%